Socio-Economic Condition and Livelihood Status of Fishers Involved in the Meghna Riverine Fish Market Chain in Bhola, Bangladesh (SAARC Journal of Agriculture, 2026)
In Bhola, Bangladesh, the fishing communities of Burhanuddin, Daulatkhan, and Tazimuddin Upazila were the focus of a socioeconomic study conducted between September 2022 and August 2023. Through focus groups and questionnaire interviews, information was gathered from sixty randomly chosen fishers in the nearby fishing village. The results indicate that 30% of the respondents were in the 30 to 40-year age range. Families with five to ten individuals often make up the greatest 65% of fishing communities' family sizes. According to the study, 73% of fisher had a joint family, and 85% of fisher are married. Here, the literacy rate was a mere 26%.  About 93% of them reside in tin sheds. Most fisher houses, 97% of them have an electricity connection, either by solar power or rural electrification. Additionally, the report revealed that 52% of fisher utilize tube wells for drinking water. Nearly every household has a private or shared enclosed pit toilet. In this study region, fisher who fish daily, over long distances, and in deep water use gear (drift gill net, set bag net, current net) and craft (non-mechanized and mechanized boat with 16–40 HP). Throughout the year, riverine fishers reportedly operate in deeper river channels, with fishing depths ranging from 30–80m. The majority of fisher's (49%) yearly earnings from fishing were between BDT 70000 and BDT 100000. Only informal microfinance NGOs, such as stubborn, Moneylender or Sailor, provide loans and giving to fishermen; but they lacked an appropriate management program, these funds were insufficient to meet their daily needs. Because of this, fishers were left defenseless amid natural disasters, banned areas, etc. To ensure sustainable livelihoods and the long-term conservation of national fisheries resources, fishers require strengthened institutional, organizational, and technical support from government organizations (GOs), non-governmental organizations (NGOs), and international NGOs (INGOs).SAARC J. Agric., 23(2): 17-33 (2025)